Turmeric oil production - Tolentino, Cesar S. (College of Engineering, 1987)
Performance of the ethanol extraction of turmeric oil from Curcuma longa Linn in a laboratory has produced the following significant results : at approximately 82 degree celcius and atmospheric pressure, treatment of ground Curcuma longa in ethanol for 45 minutes produces a percent yield of roughly 26 percent by weight. Upon determining that the maximum percent yield is reached at these conditions, they were used as the process control variables for this plant design. Previously being produced in small scale only, the high percent yield is suitable for the implementation of large scale extraction of turmeric oil such as the plant whose design and feasibility is studied in this paper. With this paper, it can be shown that the change to large scale production would increase the level of profits and therefore, would also be highly important to the development of our country's agri-tech industries. In the part about market study, the marketability of turmeric oil is discussed and is compared with other plant products as the essential oils extracted from other plants. Here it is mentioned that other indigenous plant species could produce highly marketable products. With this plant design as an example, the production of such products in large scale is possible once proper experimentation have found the process control variables for maximized percent yield and further help our country's agri-tech development.